Sociological Study Of Arabic Language On Identity Between Illusion And Reality Through Student Opinion/ دراسة سوسيولوجية للغة العربية حول الاسم بين الوهم والحقيقة من خلال دراسة لرأي الطلاب - Alabri, Khalid Hassan (Ijaz Arabi Journal of Arabic Learning, 2024)
This research aims to discuss the topic of using anonymous and fake names instead of real names, hiding the identities of internet users, and the adverse effects of disguise. This research is a case study type. The research subjects are King Fahd University of Petroleum and Minerals (KFUPM) Saudi Arabia students, with 80 students in semester 222 represented by the academic year 2023. Data collection techniques using surveys, observations, and documentation. The results: using anonymous and fake names can affect numerous aspects of a person's lifestyle, such as religious, social, ethical, and even safety. Hiding an identity allows a person to do what they could not in their real name, such as showing bad morals, spying on others, weakening family bonds, violating security, and promoting terrorism. It also discusses the treatment of this trend, whether related to the anonymous person or others who suffer consequences.